THE INFLUENCE OF COMPETENCE AND INNOVATION ON LECTURER PROFESSIONALISM AT THE INDONESIAN MARITIME ADIGUNA POLYTECHNIC MEDAN - Saima Rambe; Nurul Dalimunte (Jurnal Mantik, 2022)
In simple terms, education is a learning process for students to be able to understand, understand, and be more critical in thinking. This article aims to determine the effect of competence, innovation on professionalism. Education can occur anytime and anywhere, both on campus (school) and outside campus, which aims to develop the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative. being independent and being a democratic citizen is also responsible. The sample in this study amounted to 35 people. Analysis of hypothesis testing using SPSS Research results Partially, competence has a significant effect on lecturer professionalism at the Indonesian Maritime Adiguna Polytechnic Medan. Partially, innovation has a significant effect on the professionalism of lecturers at the Adiguna Maritime Indonesia Polytechnic, Medan. Simultaneously, competence and innovation have a significant influence on the professionalism of lecturers at the Indonesian Maritime Adiguna Polytechnic Medan.